Efektivitas Media Pink Tower untuk Meningkatkan Kemampuan Seriasi bagi Anak Disabilitas Intelektual Sedang (Single Subject Research Kelas II di SLB Autisma YPPA Bukittinggi) - Regina, Natasya; Iswari, Mega; Safaruddin, Safaruddin; Nasri, Yosa Yulia (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research is motivated by the problems that researchers found at SLB Autisma YPPA Bukittinggi where a child with moderate intellectual disabilities had difficulty in seriation ability. This study aims to determine the effectiveness of pink tower media in improving seriation ability in children with moderate intellectual disabilities class II at SLB Autisma YPPA Bukittinggi. The study used a quantitative research type with an experimental approach in the form of Single Subject Research (SSR) with an A-B design. The subjects in this study were moderate intellectual disabilities class II at SLB Autisma YPPA Bukittinggi. Furthermore, data collection used a test technique consisting of several questions. Then using data analysis techniques with visual graphics. The results of the study showed that in the baseline condition (A) which was carried out three times, a stable percentage of 33% was obtained. In the intervention condition (B) which was carried out eight times, the stable percentage was 100%. Based on the results of the study, it can be concluded that the pink tower media can improve seriation ability in children with moderate intellectual disabilities.